Gender and Nation - Yeliz Kendir-Gök (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This paper presents a comprehensive review of Gender and Nation, an invaluable academic contribution authored by the pioneer in the field of social sciences, Nira Yuval-Davis. Conducted through a gender analysis lens, this review thoroughly examines Yuval-Davis’s substantial academic legacy. Yuval-Davis’s insights emphatically underscore the heightened relevance of such a perspective when dissecting intricate issues related to nation and nationalism. The review initiates by positing a pivotal question and subsequently accentuates the gaps present within the current body of literature that addresses the intersection of nation and gender. Moreover, the review highlights the inherent worth of Yuval-Davis’s work by meticulously exploring its implications for themes encompassing women, femininity, men, masculinity, and their intricate connections with the construct of the nation. This exploration distinctly underscores the pivotal role of gender in shaping and influencing these multifaceted aspects. Consequently, the review expounds upon how our identities as gendered individuals often relegate us to a subordinate position, ultimately situating us with paramount significance in the intricate tapestry of the nation.